2015
DOI: 10.1186/s12879-015-0908-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of dengue virus reveals the high relatedness between imported and local strains during the 2013 dengue outbreak in Yunnan, China: a retrospective analysis

Abstract: BackgroundAn outbreak of dengue virus (DENV) occurred in Yunnan province. More than 2,000 individuals were infected from August to November 2013. In this study, we aimed to characterize the origin and prevalence of DENV in Dehong prefecture of Yunnan province using phylogenetic and evolutionary analyses of DENV strains collected from local patients and foreign travelers.MethodsA total of 41 DENV-positive serum samples were randomly collected from travelers who entered China at Ruili port or local patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Most local dengue cases engaged in trade activities with Burmese around. The strains detected in Dehong were from local dengue cases and imported cases, and the imported cases were all from Myanmar [20]. The phylogenetic analysis indicated that the dengue viruses detected in Dehong were classified into genotype I in DENV 1 and Asian I genotype in DENV 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most local dengue cases engaged in trade activities with Burmese around. The strains detected in Dehong were from local dengue cases and imported cases, and the imported cases were all from Myanmar [20]. The phylogenetic analysis indicated that the dengue viruses detected in Dehong were classified into genotype I in DENV 1 and Asian I genotype in DENV 2.…”
Section: Discussionmentioning
confidence: 99%
“…Because the E-gene data were downloaded from GenBank, we are unable to obtain the exact epidemiological information of each single sequence. Among the three Provinces with dengue outbreaks in 2013, we tried to assess whether the cases in Yunnan Province were local cases or not from published papers regarding its outbreak [19, 20]. For Henan and Guangdong Provinces, we contacted the Provincial CDCs, and confirmed that the sequences deposited to GenBank were all from local cases.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus neighbor-joining trees were obtained from 1000 bootstrap replicates. 8 The red-filled circles and blue-filled squares indicate DENV-2 isolated from Kaohsiung and Tainan in the 2015 severe DF outbreak. The black-outlined and black-filled squares indicate the 2014 outbreak-associated DENV-1 isolates and 2015 DENV-1 epidemic strains in Kaohsiung city.…”
Section: Figurementioning
confidence: 99%
“…Phylogenetic analysis (a neighbor-joining tree with p -distance inferred with 1000 bootstrap replicates in MEGA program version 5 for a 1485-nt fragment spanning the full gene of the envelope glycoprotein) 8 proved that the DENV-2 isolated in Kaohsiung after August clustered with the 2015 outbreak-associated DENV-2 Tainan strain (bootstrap value was 100). However, it did not cluster with previous Taiwanese epidemic DENV-2 isolates (Figure 1A, left).…”
mentioning
confidence: 99%
“…Improved treatment for dengue fever (DF) has decreased the case fatality rate by approximately half with each decade since 1980 [6]. Dengue has replaced malaria to become another threat to public health along the China-Myanmar border [7,8] as malaria has been successfully controlled [9]. More prompt and proper interventions are needed now because of the unavailability of anti-dengue drugs and low efficacy of current dengue vaccines [10,11].…”
Section: Introductionmentioning
confidence: 99%